Beta carotene-loaded zein nanoparticles to improve the biopharmaceutical attributes and to abolish the toxicity of methotrexate: a preclinical study for breast cancer. (31st October 2018) - Jain, Ashay; Sharma, Gajanand; Kushwah, Varun; Ghoshal, Gargi; Jain, Atul; Singh, Bhupinder; Shivhare, U. S.; Jain, Sanyog; Katare, O. P.
Abstract: Beta carotene (βC) loaded nanoparticles of zein (βC-NPs) were developed using modified phase separation technique. βC-NPs were prepared using different zein concentration and optimized formulation was selected on the basis of micromeritics properties and entrapment efficiency. Further, βC-NPs were evaluated for in vitro release, in vitro cell-survival, cellular localization and apoptosis induced in MCF-7 cells. The combined effect of the βC and its nanoparticulate counterpart with MTX was evaluated thereafter for cytotoxicity and apoptotic activity in MCF-7 cells. In comparison to free βC, the βC-NPs demonstrated noteworthy improvement in various biopharmaceutical attributes viz C max (∼2.3-folds), AUCtotal (2.7-folds), t 1/2 (∼1.5 folds) and MRT (∼1.5 folds), further indicating the remarkable increment in oral bioavailability of βC after incorporation in zein nanoparticles. The anti-tumour potential of prepared βC-NPs and effects of free βC and βC-NPs were investigated upon anticancer efficacy of methotrexate (MTX) in experimentally induced breast cancer rat model. Protective role of βC on MTX-associated hepatic toxicity in wistar rats was also determined using haematological and histopathological approaches. In a nutshell, zein nanoparticles improved the cellular uptake, cytotoxicity and exhibited enhanced oral biopharmaceutical performance of βC. This combination regimen could also be promising platform to facilitate the therapeutic benefits of anticancer agents. Graphical Abstract: UF0001